Effects of seawater temperature on sound characteristics in Ophidion rochei (Ophidiidae). Issue 2 (14th July 2015) - Kéver, L.; Boyle, K. S.; Parmentier, E.
<x xml:space="preserve">Abstract</x> Although the sound production mechanisms of male and female Ophidion rochei (Ophidiidae) differ significantly, temperature affects them in the same manner. In both sexes, temperature correlated negatively with pulse period and positively with sound frequencies but had no, or weak effects on other sound characteristics.